Cutaneous Plasmacytosis: Diagnostic and Therapeutic Challenge in a Patient with an Atypical Presentation - Gustavo Moreira Amorim; Ariel Córdova Rosa; Joana Buratto; Solange Emanuelle Volpato Steckert; Roberto Moreira Amorim Filho; Gabriella Di Giunta Funchal (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Cutaneous plasmacytosis is a rare dermatosis that is classically characterized by the presence of multiple papules and reddish- -brown nodules mainly in the trunk. It most commonly affects elderly Asians, with few reports in Caucasians and young patients. On histopathology there is a polyclonal proliferation of mature plasm cells. The objective of this report is to present a case of atypical manifestation of this rare disease, both due to clinical and epidemiological aspects.